Repressed Central Carbon Metabolism and Its Effect on Related Metabolic Pathways in Cefoperazone/Sulbactam-Resistant Pseudomonas aeruginosa - Chen, Yue-tao; Yang, Ke-xin; Dai, Zhen-yuan; Yi, Huan; Peng, Xuan-xian; Li, Hui; Chen, Zhuang-gui (Frontiers in Microbiology, 2022)
Metabolic shift and antibiotic resistance have been reported in Pseudomonas aeruginosa. However, the global metabolic characteristics remain largely unknown. The present study characterizes the central carbon metabolism and its effect on other metabolic pathways in cefoperazone-sulbactam (SCF)-resistant P. aeruginosa (PA-RSCF). GC-MS based metabolomics shows a repressed central carbon metabolism in PA-RSCF, which is confirmed by measuring expression of genes and activity of enzymes in the metabolism. Furthermore, expression of the genes that encode the enzymes for the first step of fatty acid biosynthesis, glutamate metabolism, electron transport chain, and riboflavin metabolism are reduced, confirmed with their enzymatic activity assay, indicating the decreased metabolic flux to the four related metabolic pathways. Moreover, the role of the reduced riboflavin metabolism, being related to ROS generation, in SCF resistance is explored. Exogenous H2O2 potentiates SCF-mediated killing in a dose-dependent manner, suggesting the decreased ROS is resulted from the reduced riboflavin metabolism that contribute to the resistance. These results indicate that the repressed central carbon metabolism and related riboflavin metabolism contributes to SCF resistance but increasing ROS can restore SCF sensitivity. These findings characterize the repressed central carbon metabolism and its effect on other metabolic pathways as the global metabolic features in PA-RSCF.